The Role of Housekeeping in Maintaining the Image and Guest Satisfaction at Tunjungan Hotel Surabaya, East Java - R. Paulus Widyalasmono W. S (The Postgraduate School of Tourism Sahid Polytechnic, 2026)
This study aims to analyze the role of the housekeeping department in maintaining the image and guest satisfaction at Hotel Tunjungan Surabaya, East Java. Using the SERVQUAL theory (Valarie A et al., 1988), corporate image theory (Dowling, 2001), and customer satisfaction theory (Oliver et al., 1997), this research employs a qualitative approach with data collected through interviews with the housekeeping manager, staff, and several hotel guests. The results show that housekeeping services have a positive impact on shaping the hotel’s image and guest satisfaction, although several challenges remain, such as limited workforce and varying guest expectations regarding cleanliness standards. Fast, friendly, and consistent service reflects good work quality, with guest satisfaction indicated by positive perceptions of room cleanliness and comfort. This success demonstrates that housekeeping plays an essential role in strengthening the hotel’s image as a clean, comfortable, and professional place to stay, although further improvements are needed in staff training and interdepartmental coordination. The conclusion of this study is that housekeeping contributes significantly to building a positive hotel image and enhancing guest satisfaction through quality service that prioritizes customer needs. Therefore, it is recommended that Hotel Tunjungan management continue to improve the competence of housekeeping staff, strengthen work systems, and maintain consistent cleanliness standards to ensure the hotel’s positive image is sustained in the long term.